Reflections on Java and Islam 1979-2010 - Woodward, Mark (Al-Jamiah Research Centre, 2011)
Since the late 1970s, technological developments, especially in communications and transportation, have contributed to growth of new modes of social interaction and, at the same time, to the strengthening of social bonds in geographically dispersed social groups and communities in Yogyakarta. Increased educational opportunities and especially the development of the Islamic university system have contributed to the development of a Muslim middle class and with it a Muslim consumer culture. There has also been a significant shift in the ways in which relationships between culture (kebudayaan) and religion (agama) are conceptualised. Elements of Javanese Muslim tradition including prayer meals (slametan) that were formerly called agama are now more commonly referred to as kebudayaan. This shift reflects and has contributed to the diminution of sectarian conflict. This cultural strategy is not always successful. It does, however, provide a basis for proactive measures to counter sectarian violence. This is evident in âculturalâ festivals supported by the kraton (palace) in response to attacks on cultural performance events by exclusivist religious groups.[Sejak dekade 1970an, kemajuan teknologi, utamanya dalam komunikasi dan transportasi, telah mengubah cara interaksi sosial masyarakat Yogyakarta dan, pada saat yang sama, semakin memperkokoh ikatan antar kelompok sosial. Semakin meningkatnya kesempatan belajar [sekolah], utamanya dengan berdirinya Universitas Islam, terbukti mendorong terciptanya kalangan âMuslim kelas menengahâ sekaligus konsumerisme yang melekat pada kalangan tersebut. Selain itu, terjadi pula perubahan konsep dalammenilai agama dan kebudayaan. Beberapa bentuk tradisi Islam Jawa, seperti slametan, yang dulunya dinilai sebagai ritual agama, saat ini hanya disebut sebagai kebudayaan. Perubahan ini menggambarkan dan bahkan berperan dalam meminimalisir konflik sektarian, seperti terlihat jelas dalam acara festival âbudayaâ yang diadakan kraton sebagai respon terhadap pembubaran pementasan budaya oleh kalangan Muslim ekslusif.]